The FinTech phenomenon: antecedents of financial innovation perceived by the popular press - Liudmila Zavolokina; Mateusz Dolata; Gerhard Schwabe (Financial Innovation, 2016)
The financial industry has been strongly influenced by digitalization in the past few years reflected by the emergence of 'FinTech,' which represents the marriage of 'finance' and 'information technology.' FinTech provides opportunities for the creation of new services and business models and poses challenges to traditional financial service providers. Therefore, FinTech has become a subject of debate among practitioners, investors, and researchers and is highly visible in the popular media. In this study, we unveil the drivers motivating the FinTech phenomenon perceived by the English and German popular press including the subjects discussed in the context of FinTech. This study is the first one to reflect the media perspective on the FinTech phenomenon in the research. In doing so, we extend the growing knowledge on FinTech and contribute to a common understanding in the financial and digital innovation literature. These study contributes to research in the areas of information systems, finance and interdisciplinary social sciences. Moreover, it brings value to practitioners (entrepreneurs, investors, regulators, etc.), who explore the field of FinTech.
Keywords: 650; FinTech; Innovation; Digitalization; Content analysis; Popular press